A difficult case: Severe learning difficulties and patient selection. (September 2013) - Ford, John; Bradley, Jane
<x content-type="archive" xml:space="preserve">Abstract</x> This paper describes the assessment and subsequent cochlear implantation of a young person with progressive sensorineural hearing loss. He is diagnosed with trisomy 3P syndrome and has severe learning difficulties and global developmental delay. The assessment process is described, together with the rationale for decision-making and the early progress and benefit received from the cochlear implant. Consideration is given to the factors which enabled the successful outcome.